The role of European union law in ensuring the protection of vulnerable groups during humanitarian crises - Subbota, Anastasiia (Global Prosperity, 2025)
Abstract. The weaknesses in a legal system are showing when a humanitarian crisis occurs, and especially, when it comes to the safeguarding of an individual and/or group in a position of vulnerability. The crises in Europe over the last couple of years, especially the European Union’s multi-phase crises of mass displacement due to war, have challenged the Centre of EU Law to respond to the Displacement and Protection Crisis in a timely manner, and in a framework of effective and entitled protection. The Purpose of this Paper is to illustrate the impact of EU law on the protection of the vulnerable in times of humanitarian crisis, particularly of vulnerable asylum seekers, refugees, displaced persons and/or children. The authors rely solely on the legislative acts and legal instruments of the European Union, and the legal doctrines of the most recent literature on the legal protection of the vulnerable, to assess the degree of attention that the legal systems of the European Union devote to vulnerable protection. Besides the attention given to the Protective Measures of the European Union in response to the Ukraine Crisis, this Paper intends to document the story of the European Union’s legal protection of the vulnerable in a humanitarian crisis. While the author recognizes the finesse of the European Union’s legal system in designing rules to protect the vulnerable, the author stresses that the rules have severely neglected consistent application, individual consideration, and collaboration to protect the vulnerable at the intra and inter-state levels. The author proposes the creation of effective mechanisms of protection, along with legal clarity, by providing a structure to the application of the concept of vulnerability that is humanitarian, inter-sectional, and focused on the rights of the vulnerable.